Технологія модульного навчання як репрезентатор гуманізації навчально-виховного процесу - Корнієнко, Л. М. (НТУ "ХПІ", 2015)
У статті аналізуються основні тенденції розвитку вітчизняної освіти. Обґрунтовується необхідність переходу освіти на технологічний рівень, що відповідає завданням гуманізації навчально-виховного процесу. Засобом такої гуманізації автор вважає технологію модульного навчання, яка орієнтована на особистість, означає максимальну індивідуалізацію і диференціацію навчального процесу.

The author analyses the main trends of the development of our system of education. Great attention is paid to the transition of education to the technological level according to the tasks of present-day life. The technology of modular teaching is considered to be perspective for humanisation of teaching and educative procedure that is oriented into personality and means maximum individuality, differentiation of educational process.
Technology of modular instructions as the representative means of teaching and educational process humanisation
Keywords: інноваційні технології навчання; активізація учіння; оптимізація навчального процесу; ідея гуманізації; індивідуалізація; диференціація навчального процесу; мотивація; самореалізація; педагогічний процес; innovative teaching technologies; modular teaching technology; teaching process optimisation; idea of humanisation; motivation; pedagogical process